2022
DOI: 10.3390/ijerph19074087
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Disaster-Related Deaths in the Great East Japan Earthquake: A Retrospective Observational Study Using Data from Ishinomaki City, Miyagi, Japan

Abstract: Disaster-related deaths are of two types: direct and indirect. Preventable disaster-related deaths reported in the Great East Japan Earthquake (GEJE) included a large number of indirect deaths. This study aimed to investigate the data on disaster-related deaths in the GEJE in Ishinomaki City, Miyagi Prefecture, and to clarify the scope of disaster-related deaths to help future disaster preparedness. A retrospective observational study was conducted using public data on disaster-related deaths from March 2011 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…On 11 March 2011, the Great East Japan Earthquake (GEJE) revealed that 3784 disaster-related deaths had occurred since September 2021. The Fukushima Prefecture was particularly affected by the Fukushima Daiichi Nuclear Power Plant (FDNPP) accident, with over 2329 (60%) disaster-related deaths, indicating its severe impact [7]. In addition, the health effects of the FDNPP accident were multifaceted and long-term, distinct from previous disaster-related deaths [8].…”
Section: Introductionmentioning
confidence: 99%
“…On 11 March 2011, the Great East Japan Earthquake (GEJE) revealed that 3784 disaster-related deaths had occurred since September 2021. The Fukushima Prefecture was particularly affected by the Fukushima Daiichi Nuclear Power Plant (FDNPP) accident, with over 2329 (60%) disaster-related deaths, indicating its severe impact [7]. In addition, the health effects of the FDNPP accident were multifaceted and long-term, distinct from previous disaster-related deaths [8].…”
Section: Introductionmentioning
confidence: 99%
“…It has been pointed out that the poor environment of evacuation shelters causes health problems and disaster-related deaths among evacuees, and we are concerned that their environment will deteriorate, particularly during a large-scale disaster such as a Nankai Trough earthquake due to a shortage of daily necessities ( Ichiseki, 2013 ; Tsuboi et al, 2022 ). According to the third edition of the Nankai Trough Earthquake Countermeasures Plan, approximately 4.4–9.5 million people are expected to be evacuated 1 week after an earthquake, which is 20 times the number of evacuees in the Great East Japan Earthquake ( Cabinet Office of the Government of Japan, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to the third edition of the Nankai Trough Earthquake Countermeasures Plan, approximately 4.4–9.5 million people are expected to be evacuated 1 week after an earthquake, which is 20 times the number of evacuees in the Great East Japan Earthquake ( Cabinet Office of the Government of Japan, 2013 ). Physical and mental fatigue caused by living in evacuation shelters accounted for 33% of disaster-related deaths in the Great East Japan Earthquake, and it has been reported that 20% of evacuees complained of back pain ( Ichiseki, 2013 ; Tsuboi et al, 2022 ). Japanese evacuees were used to sleeping directly on the floors of school classrooms or gymnasiums, but cardboard beds have been installed since the Great East Japan Earthquake ( Nara et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…2 Also, in the 2011 Great East Japan Earthquake, there were reports of problems in the medical system, such as delays in medical intervention due to a lack of information and indirect disaster-related deaths due to the poor evacuation environment. [3][4][5] Focusing on specific disasters, during the 2007 Niigata Chuetsu-oki earthquake, a small amount of radioactive material was detected leaking from a nearby nuclear power plant. At that time, there was no impact on the public or the environment, but there was also a case where insufficient radiation information was provided to the Japan Disaster Medical Assistant Team (DMAT), and there was a problem with dispatching to the site due to anxiety.…”
Section: Introductionmentioning
confidence: 99%